Evaluation of the patient with temporomandibular dysfunction : what are the steps to arrive at a correct diagnosis? - Januzzi, Eduardo (2017)
Temporomandibular disorders are heterogeneous group of disorders involving the temporomandibular joint, masticatory muscles and associated structures. With a multifactorial origin, usually the patient with mandibular temporomandibular disorder reports multiple complaints, associated or not to comorbidities and non-repairing sleep. Anamnesis directed to the correct diagnosis is fundamental for the elaboration of a successful therapy. The diagnostic process should be able to categorize the pain as well as identify the involved tissues in addition to pointing out the specific source of pain within that tissue system. The steps to arrive at a correct diagnosis should cover: anamnesis, clinical evaluation for temporomandibular joint, the clinical examination through inspection of the cranial nerves, intra-oral evaluation and musculoskeletal examination, imaging tests, anesthetic block diagnosis, laboratory tests and evaluation of sleep pattern. This process begins in the clinical history, presence or not of associated comorbidities, sleep pattern and other factors that may somehow contribute to the patient’s clinic. This information supports the correct diagnosis and is essential for adequate and successful therapy.